Monetising the dividual self : the emergence of the lifestyle blog and influencers in Malaysia - Hopkins, Julian (Anthropologist) (New York : Berghahn Books, 2019)
"Combining theoretical and empirical discussions with shorter thick description case studies, this book offers an anthropological exploration of the emergence in Malaysia of lifestyle bloggers--precursors to current social media microcelebrities and influencers. It tracks the transformation of personal blogs, which attracted readers with spontaneous and authentic accounts of everyday life, into lifestyle blogs that generate income through advertising and foreground consumerist lifestyles. It argues that lifestyle blogs are dialogically constituted between the blogger, the readers, and the blog itself, and challenges the assumption of a unitary self by proposing that lifestyle blogs can best be understood in terms of the dividual self"--
Brief chronology of personal and lifestyle blogging in Malaysia -- Introduction : Anthroblogia : participant observation and blogging in Malaysia -- The blogs as assemblage : agency and affordances -- January 2006 : blogwars, hit sluts, and authenticity in the personal blogosphere -- The blogger and her blog : (dis)assembling the dividual self -- May 2007 : the assembling of genres -- Assembling blogs and bloggers -- April 2007 : voicy consumers and negotiating networked publics -- Assembling a blog market -- January 2009 : negotiating the authentic advertorial -- Assembling lifestyles -- October 2009 : regional blogmeet -- Conclusions : the dividual self and emergence of the lifestyle blog.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on February 18, 2019).
JSTOR
Keywords: Blogs -- Social aspects -- Malaysia; Bloggers -- Malaysia; Lifestyles -- Malaysia; Social influence; Consumption (Economics) -- Social aspects -- Malaysia; Blogues -- Aspect social -- Malaisie; Blogueurs -- Malaisie; Style de vie -- Malaisie; Influence sociale; Société de consommation -- Aspect social -- Malaisie; LITERARY COLLECTIONS / Essays; SOCIAL SCIENCE / Anthropology / Cultural; Bloggers; Consumption (Economics) -- Social aspects; Lifestyles; Social influence; Malaysia